Sex-specific incident dementia in patients with central nervous system trauma - Mollayeva, Tatyana (Alzheimers Dement (Amst), 2019)
INTRODUCTION: Despite evidence that central nervous system (CNS) trauma, including traumatic brain injury and spinal cord injury, can cause sustained neurocognitive impairment, it remains unclear whether trauma-related variables are associated with incident dementia independently of other known risk factors. METHODS: All adults without dementia entering the health-care system with diagnoses of CNS trauma were examined for occurrence of dementia. All trauma-related variables were examined as predictors in sex-specific Cox regression models, controlling for other known risk factors. RESULTS: Over a median follow-up of 52 months, 32,834 of 712,708 patients (4.6%) developed dementia. Traumatic brain injury severity and spinal cord injury interacted with age to influence dementia onset; women were at a greater risk of developing dementia earlier than men, all other factors being equal. DISCUSSION: Risk stratification of patients with CNS trauma by sex is vital in identifying those most likely to develop dementia and in understanding the course and modifying factors.